Dinamika Faktor Risiko Makroekonomi pada Return Saham Sektor Energi: Pendekatan Arbitrage Pricing Theory - Erna Garnia; Tahmat Tahmat; Pipit Muditya Harjo Singgih; Siti Riyyan Lisaumi; Usep Rendiana (Pusat Riset dan Inovasi Nasional, 2026)
sector in Indonesia faces significant exposure to external macroeconomic shocks, yet the understanding of how these risk factors dynamically influence stock returns across different political-economic regimes remains limited. This study investigates the influence of six exteral factors Global Index, macroeconomic variables, world oil prices, China Index, Arabian Index, and competitive resources on energy sector stock returns during two presidential admitrtions: Susilo Bambang Yudhoyono (2004-2014) and Joko Widodo (2014-2021). The research employs Arbitrage Pricing Theory (APT) as the theoretical framework to examine whether these macroeconomic risk factors demonstrate regime-dependent pricing dynamics. Using panel data regression analysis on monthly observations spanning 17 years, energy stocks are categorized into high-return and low-return portfolios to assess differential sensitivity across performance groups. The methodology includes best model selection, classical assumption tests, hypothesis testing, and dummy variable analysis to detect regime differences. Results indicate that all six factors simultaneously influence stock returns across both periods. Partial analysis reveals that Global Index, China Index, and Arabian Index significantly affect returns during SBY's administration, while Jokowi's era shows expanded sensitivity including world oil prices alongside previously significant factors. Tests for differential effects between portfolio groups yield mixed results across regimes. The study concludes that while external macroeconomic factors significantly drive energy sector performance, their influence magnitude does not consistently differ between high and low-return groups, suggesting uniform market-wide sensitivity to systematic risk factors regardless of individual stock performance characteristics.